THE INFLUENCE OF LIQUIDITY, COMPANY SIZE, AND SOLVENCY ON FINANCIAL PERFORMANCE (Case Study on the 10 Largest Banks Listed on the Indonesia Stock Exchange During the Period 2018-2022) - Fitriyah, Ratna Shofiyatul; Suwardi , Suwardi; Hartono, Djoko Setyo (Economics and Business International Conference Proceeding, 2024)
This study aims to determine the influence of liquidity, company size, and solvency on company performance. The sampling technique used is purposive sampling involving the 10 largest banks listed on the IDX in the years 2018-2021. The data used are secondary data in the form of companies' annual financial reports using multiple regression analysis. All testing in this study used SPSS software version 27. The test results reveal that the coefficient of determination (R2) is 0.427, meaning that the independent variables affect the dependent variable by 42.7%, with the remaining 57.3% influenced by other variables outside the scope of this research. The F-test results show that the independent variables Loan to Deposit Ratio (LDR), Firm Size (SIZE), and Debt to Asset Ratio (DAR) collectively have a positive impact on the dependent variable Return on Assets (ROA). The t-test results show that the variable Firm Size (SIZE) positively affects Return on Assets (ROA). Meanwhile, Loan to Deposit Ratio (LDR) and Debt to Asset Ratio (DAR) have a negative effect on Return on Assets (ROA). The negative sign in the t-value indicates an inverse relationship between the variables LDR and DAR with the variable ROA.